Internal erosion of soil pipes: Sediment rating curves for soil pipes. Issue 15 (13th October 2020) - Wilson, G.V.; Ursic, M.; Fox, G.A.; Nieber, John L.
Abstract: The collapse of soil pipes due to internal erosion can result in fully mature gullies. Few studies have measured the rates of sediment detachment and transport through soil pipes in situ . The objectives of this work were to determine suspended sediment concentration (SSC) in soil pipes as a function of pipeflow rate to develop sediment rating curves (SRC) and measure the bedload transport as a function of cumulative flow per storm event. H‐flumes were installed in seven discontinuous gullies formed by pipe collapse and instrumented for pipe discharge measurements and suspended sediment sampling. The typical response to pipeflow was an initial flush of high concentration of suspended sediment followed by a decrease as pipeflow increased (rising limb of hydrograph). Pipeflows were often so dynamic that it was difficult to consistently capture the initial flush of sediment, resulting in weak to non‐existent SRCs. The falling limb of the hydrograph tended to have a relatively low SSC. Thus, soil pipe SRCs tended to be better represented by hysteretic SRCs, although relationships between SSC and flow rate were poorly represented by SRCs. A power law equation given by SSC =  aQ b was adopted to represent the SRC relationships. Fitting this equation to data showed a correlation between the offset, a, and the slope, b, with the slope decreasing as the offset increases. Both SRC parameters ( a and b ) were correlated to the contributing area of the individual pipe. Bedload appeared to be an important contributor to sediment transport, with bedload – expressed as an average event sediment concentration (mg l −1 ) – decreasing as the volume of the event discharge (m 3 ) increased. A significant portion (11–31%) of the bedload material was gravel and aggregates (>2 mm diameter material). While this work was the first to determine SRCs for soil pipes, refined sampling and measurement techniques are needed. © 2020 John Wiley & Sons, Ltd. Abstract : Sediment rating curves (SRCs) for soil pipes developed from measurements of suspended sediment concentrations and pipeflows. Hysteretic SRCs were generally superior to non‐hysteretic SRCs and falling limb SRCs were superior to rising limb SRCs. Soil loss by bedload transport also measured for individual soil pipes.